THE USE OF SCRAMBLED WORD GAME ON STUDENTS VOCABULARY - Sakinah, Vanila (Journal of English Teaching and Linguistics Studies (JET Li), 2022)
Learning vocabulary is often monotonous because the teacher only asks the students to do the worksheet without giving activities to make them enjoy learning. For that reason, the teacher needs an appropriate medium that can offer a fun learning process and attract the students interest. One of the teaching mediums is scrambled word games. The aim of this research is to investigate the use of scrambled word games on students vocabulary retention. The population of this research is the first-grade students of SMP Negeri 3 Cikembar. The total number of samples are 10 students of class VII-B. The sample is chosen by simple random sampling technique. In conducting this research, the writer applies a pre-experimental method and uses one group pretest-posttest design. The writer gives pre-test, two treatments, and post-test to the students. Vocabulary test is given to measure the students vocabulary in descriptive text as the topic. The data is analyzed by using the t-test formula. Based on the calculation of the data, the mean of the difference is 12.6 and the total of deviation of difference is 764.4. In conclusion, the final result shows that the use of scrambled word games has an effect on students vocabulary retention.